PENGARUH EARNING PER SHARE (EPS), DEBT TO EQUITY RATIO (DER) DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM PT. ASTRA AGRO LESTARI TBK - Iin Syofia Yandra (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to determine: 1). Is there any effect of Earning Per Share on the Stock Price? 2). Is there any influence of the Debt-to-Equity Ratio on the Stock Price? 3). Is there any effect of Net Profit Margin on the Stock Price? 4). Is there any effect of Earning Per Share, Debt to Equity Ratio and Net Profit Margin on the Stock Price? 5). How big is the influence of Earning Per Share, Debt to Equity Ratio and Net Profit Margin on the Stock Price? The analytical tool used in this research is multiple linear regression analysis which is logged with the help of statistical software version 26. The data sources are from the IDX financial report data, the IDX website (www.idx.co.id) and the yahoo finance website (http: //finance.yahoo.com) The data collection technique was carried out using library research techniques. Based on the results of the study indicate that: There is no effect of EPS on stock prices partially in this study, where the value (-0.970 <2.447) with a significant level is 0.370> 0.05. There is no partial effect of DER on stock prices in this study, where the value (0.468 <2.447) with a significant level is 0.656> 0.05. There is no partial effect of NPM on stock prices in this study, where the value (1.038 < 2,447) with a significant level is 0.339> 0.05. There is no effect of EPS, DER and NPM on stock prices simultaneously in this study, where the Fcount value is smaller than the Ftable value or 0.737 <4.76 and the significant value is 0.567>0.05. The magnitude of the influence between EPS, DER and NPM on stock prices is 0.269% or (0.5192x100%=26.9%). This shows that 26.9% is the contribution of EPS, DER and NPM variables to the stock price at PT. Astra Agro Lestari, Tbk in 2013-2022 while the remaining 73.1% (100%-26.9%) can be explained by other variables outside the research variables